Symmetry-Correlated Component in the Visual-Evoked Potential: Electrophysiological Study of Visual Symmetry Perception in Humans - Melkie Sambul, Alwin; Murayama, Nobuki; Igasaki, Tomohiko (Neuroscience and Biomedical Engineering (Discontinued), 2015)
Humans are able to perceive symmetry information in the visual environment rapidly and efficiently. Although the psychophysical aspects of visual symmetry recognition have been investigated, relatively little attention has been paid to understanding their underlying neural mechanisms. This study aimed to investigate human visual-evoked potentials (VEPs) in response to complex object images of varying symmetry, and to find their neural correlates. The stimuli consisted of five gray-scale images of daily life objects (flower, butterfly, human face, bird, and car) with different levels of horizontal and vertical symmetry that were quantified using the images’ pixel values, and by subjective evaluation by the participants. VEPs were extracted from the electroencephalogram (EEG) data recorded using 128-channel scalp electrodes in 11 healthy human subjects. The results revealed a significant correlation between latency differences of the VEP component at occipito-temporal sites around 170 ms (N170) and the levels of stimulus symmetry.
Keywords: horizontal symmetry